El planeta frente a la salud pública, nuevo horizonte de investigación (2021)
In the months of confinement, the world stopped, but nature continued on its way, recovered and had a break. This temporary relief was a call for the academy and the governments to bet on more research and to strengthen political instruments with a socio-environmental focus.